Studi Potensi Pembangkit Listrik Tenaga Mikro Hidro Di Desa Masolo Raya Dalam Inovasi Turbin Pelton Dengan Sumbu Horizontal - Suparjo, Muhamad; Balaka, Ridway; Kadir, Kadir (Teknik Mesin Universitas Halu Oleo, 2020)
The purpose of this research is to find out how much electricity is in the mango river in the Mosolo Raya village. The research method used is to measure the flow of water with a storage method, measurement of water flow velocity, measurement of water falls height and the manufacture of Pelton turbine blades. The results showed that the largest water discharge value was 0.018182 m3/s on the 4th measurement, and the smallest water discharge value was 0.014679 m3/s on the 8th measurement, the largest speed value was 7.333225 m/s on the 4th measurement and the smallest speed value was 5.920402 m/s on the 8th measurement, the largest power value is 1215,984 watts on the 4th measurement and the smallest power value is 981.7119 on the 8th measurement. So, it can be concluded that the potential value of the mango river with the average electric power generated during the measurement is 110,779 Watt.Keywords: Power plant, horizontal axis, pelton turbine, mini hydro power